The required function is,
"\\lambda(x) = \\dfrac{1-cos(2\u03c0x)}{2}"
Comparing the function to "\\lambda(x) = q(x)(p(x) + 1)"
"\\therefore p(x) = -cos(2\u03c0x),\\\\\nand\\ q(x) =\\frac{1}{2}"
For x = 1,
"\\lambda(1) = \\dfrac{1-cos(2\u03c0(1))}{2}"
"\\lambda(1) = \\dfrac{1-cos(2\u03c0)}{2} = 0"
For x= 2,
"\\lambda(2) = \\dfrac{1-cos(2\u03c0(2))}{2}"
"\\lambda(2) = \\dfrac{1-cos(4\u03c0)}{2} = 0"
"\\therefore" when x = n,
λ(x) = λ(n) = 0
and λ(n) derived is;
"\\lambda(n) = \\dfrac{1-cos(2\u03c0(n))}{2}"
"\\lambda(n) = \\dfrac{1-cos2n\u03c0}{2}"
Comments
Leave a comment